Pendampingan Mitigasi Risiko pada UMKM Aneka Jaya Snack di Kabupaten Demak - Kurniawan, Danang; Ghofur, Muhammad Abdul (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2025)
The number of Micro, Small, and Medium Enterprises (MSMEs) in Demak Regency was recorded at 13,027 as of 2024. This substantial figure indicates a strong need for targeted development efforts, particularly in the areas of risk mitigation and management. Findings from literacy assessments and mentoring involving 22 employees revealed that none had previously participated in training related to business risk management. This community engagement program involved risk mitigation assistance for the Aneka Jaya Snack MSME, aiming to enable early risk identification, the design of appropriate risk management frameworks, understanding of risk management criteria, assessment of potential impacts, and the development of suitable risk measurement mechanisms. The activity was conducted using the Participatory Action Research (PAR) method, which included stages such as preparation, socialization, and mentoring sessions with the MSME. Through this structured assistance, participants were able to recognize the significance of risk management in supporting their daily operations. Implementing risk management strategies helps ensure business sustainability, facilitates early anticipation of possible disruptions, and supports effective decision-making based on the level of risk. Furthermore, improved understanding among employees enhances their capacity to perform optimally in the workplace.